UPAYA MENINGKATKAN HASIL BELAJAR MATEMATIKA MELALUI PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING DENGAN PENDEKATAN TEACHING AT THE RIGHT LEVEL - Nikmatul Atiyah; I Komang Sukendra; Ni Made Sri Utami Dewi (Widyadari, 2024)
The Problem-Based Learning (PBL) model with a Teaching at the Right Level (TaRL) approach not only motivates students to be more active and critical in the learning process but also ensures that each student receives attention and assistance according to their skill level. This classroom action research aims to determine whether the application of the PBL model with the TaRL approach can improve mathematics learning outcomes. The subjects of the research were the students of class VII D of SMPN 1 Kuta Utara in the academic year 2023/2024. This classroom action research was conducted in two cycles, which included initial reflection, planning, implementation, observation, and reflection. Data collection was carried out through observations and written assessments. The instruments used were observation sheets and essay questions. The data analysis technique used was descriptive analysis. The results of the research showed a significant improvement in students' mathematics learning outcomes from the pre-cycle to the second cycle. In the pre-cycle, the percentage of students achieving mastery was only 36.84%. After the application of PBL with the TaRL approach, the percentage of mastery increased to 60.05% in the first cycle and reached 78.94% in the second cycle. This improvement indicates that the application of PBL with the TaRL approach is effective in enhancing students' mathematics learning outcomes.